Active Harmonic Compensation and Stability Improvement in High-Power Grid-Connected Inverters Using Unified Power Quality Conditioner - Elham Samavati; Hamid Reza Mohammadi (International Journal of Industrial Electronics, Control and Optimization, 2023)
Multifunctional features of grid-connected inverters can be used for harmonic compensation of local load voltage and grid-injected current. But, in high-power grid-connected inverters, there is a challenge due to low switching frequency. On the other hand, simultaneous compensation of local load voltage and grid-injected current harmonics is an important issue in grid-connected inverters. Using a Unified Power Quality Conditioner (UPQC) at the Point of Common Coupling (PPC), an improved active harmonic compensation method is proposed which is appropriate for high-power low-frequency grid-connected inverters. The UPQC operates as a combination of a negative shunt virtual admittance and a negative series virtual impedance at the PCC. It suppresses the disturbances caused by local load variation and grid impedance change. Using a low-power, high-frequency UPQC, local load voltage and grid-injected current harmonics up to higher-order components are simultaneously compensated despite grid impedance changes and nonlinear local load variations. The control system is designed according to the impedance-based stability criterion to ensure the system's stability. The theoretical results are validated using different case study simulations in MATLAB/Simulink software.